CONCEPTUAL APPROACHES TO THE APPLICATION OF THE MARKETING MANAGEMENT CONCEPT AT THE ENTERPRISE - BOIKO, RUSLAN (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article highlights the main problems of applying the concept of marketing management in the enterprise. It is indicated on the relevance of the topic under conditions of market relations for enterprises. The works of scientists involved in the study of these issues have been analyzed, and insufficiently investigated aspects are singled out. It is noted that in the complex dynamic conditions of modern enterprises, the importance of management aspects in marketing activities has increased sharply, which will allow companies to survive in the competition in the long run. The activity of the enterprise working in the market of production of industrial gases of Ukraine is analyzed prospects. Its assortment policy is analyzed. The main suppliers of the enterprise have been identified. The main competitors of the enterprise are determined. The further development of the enterprise are estimated. It is noted the need to improve the management of its marketing activities. To identify problems in the work of the company was conducted marketing research through a survey of consumers of its products. At the beginning of the study, we put forward several hypotheses about the situation at the enterprise. As a result of the study, some hypotheses were confirmed and some were refuted. A marketing study of the enterprise through an expert survey. The study of the level of marketing activities of the enterprise is presented clearly in the form of a diagram. For the futher marketing study of the enterprise there were used the SWOT-analysis and the McKinsey matrix. According to its results, the main shortcomings in the organization of the enterprise are indicated, the directions of its potential development are determined. It is noted that it will be appropriate to strengthen the marketing orientation of the enterprise, which will improve the activities of the enterprise as a whole. The management of marketing activity of the enterprise on the basis of improvement of its assortment and price policy is offered.